Distance Education and Corporate Training in Brazil: Regulations and interrelationships - Stella C. S. Porto (Athabasca University Press, 2008)
Distance education in Brazil has evolved more slowly than distance education offerings in other developing countries. This is because all aspects of Brazil’s publicly-funded educational system are excessively regulated, highly bureaucratic, and tightly centralized. Such highly centralized bureaucracy and strict control has resulted in tremendous hurdles that work to thwart the adoption, provision, and diffusion of distance education. This is not good news: Like many developing countries, Brazil is also characterized by wide gaps in wealth distribution, with 20 percent of its population functionally illiterate and living below the poverty line. Distance education, therefore, could be used to help train Brazil’s citizens. Brazil’s emerging status in the global economy, however, is generating enormous opportunities that are fueling demand for change. For example, in their quest to be competitive in the emerging global economy, Brazil’s corporate sector has addressed this challenge by establishing corporate universities to train and educate their employees; much of this corporate training and education takes place online and at a distance. The established and emerging educational opportunities provided by Brazil’s corporate sector, in turn, is fuelling the demand for the provision of distance education throughout Brazil. Indeed, most Brazilians are ready for distance education. Many Brazilian households own television sets and cellular telephones, and its expanding communication infrastructure has capacity to support distance and continuing education models. Moreover, this capacity is currently being used by Brazil’s rapidly expanding corporate university sector. In spite of Brazil’s emergence in the global marketplace and its private-sector educational success stories, Brazil’s public educational institutions have not kept pace. This is due to Brazil’s long-standing stringent regulation of its public education sector. Recent public initiatives, however, such as the Open University of Brazil, do hold promise in fueling the growth of distance education to meet the needs of its citizens, poor and rich alike. This paper analyzes the evolution of distance education in Brazil. It explores interrelationship between the nation’s corporate and publicly-funded higher-education sectors, and the influences Brazil’s highly regulated distance education practices has on the corporate environment. The paper concludes with a broad-brushed overview of ‘success stories’ of Brazil’s corporate universities.